SOCIAL SUPPORT AND ITS RELEVANCE TO SELF CONTROL SPECIALLY INTENDED YOUTH IN INSTITUTIONS CLASS II PEKANBARU - Nurjanis Nurjanis (Jurnal Scientia, 2023)
The purpose of this study was to determine social support and its relevance to the self-control of specially assisted adolescents at class II institutions in Pekanbaru. The background of this research is because there are mostly teenagers who experience various psychological mental conflicts such as insults, threats or pressure, hurt and are easily offended so that they are easily ignited by uncontrolled emotions. This research is a quantitative research by distributing questionnaires to 86 respondents aged adolescents in the Pekanbaru class II special children's development institution. Data from the results of this questionnaire were then processed through SPSS (Statistical Product and Solution) 17.0 for windows with r table 0.215 so that r count was 0.631 so that r count was greater than r table. From the results of this study, a correlation coefficient of 0.631 was obtained at Sig (2-tailed) = 0.000, it turned out that Sig > 0.05 (0.631 > 0.05) then Ha was accepted and Ho was rejected. The magnitude of the correlation value in the product moment interpretation table is 0.60-0.799 indicating a strong correlation category. Thus based on the alternative hypothesis (Ha) there is a relevance of support for the self-control of specially assisted adolescents in class II Pekanbaru institutions.